2017
DOI: 10.1002/ece3.2920
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of dams, alien fish, and physiochemical environmental factors on homogeneity/heterogeneity of fish community in four tributaries of the Pearl River in China

Abstract: In this study, we aimed to characterize the fish community structure and identify the drivers contributing to homogenization/differentiation processes in four tributaries to the Pearl River, Guangxi Province, China, over the past few decades. We sampled 22 sites seasonally from 2013 through 2015, and these sites were selected based on archived records of previous sampling conducted in the 1980s. Jaccard's faunal similarity index, cluster analysis, and canonical correspondence analysis (CCA) were applied to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 74 publications
1
14
0
1
Order By: Relevance
“…These findings expand on previous studies reporting incipient homogenization among the Chilean ichthyological provinces [41,42] and within the Neotropical realm [15,73]. A first implication of our results is that the Chilean basins share the generalized (global) homogenization trends, also recorded in other countries such as Australia [74], China [18][19][20], Japan [17], Portugal-Spain [13,75], European countries [76], and United States [11,12]. The importance of the analyses based on countries as study units lies in that-if biotic homogenization is an undesired byproduct of global biotic change [10]-it would be more feasible to stop or to revert, because countries can take appropriate actions and use political tools for their territorial management [77].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings expand on previous studies reporting incipient homogenization among the Chilean ichthyological provinces [41,42] and within the Neotropical realm [15,73]. A first implication of our results is that the Chilean basins share the generalized (global) homogenization trends, also recorded in other countries such as Australia [74], China [18][19][20], Japan [17], Portugal-Spain [13,75], European countries [76], and United States [11,12]. The importance of the analyses based on countries as study units lies in that-if biotic homogenization is an undesired byproduct of global biotic change [10]-it would be more feasible to stop or to revert, because countries can take appropriate actions and use political tools for their territorial management [77].…”
Section: Discussionsupporting
confidence: 89%
“…Although homogenization studies in freshwater fish assemblages are increasing, most part of them come from temperate latitudes of the Northern Hemisphere [e.g., [11][12][13][14][15][16][17][18][19][20], evidencing a remarkable geographical bias. Because the species diversity is differentially distributed between hemispheres, continents, and regions [2], it is desirable to know whether biotic homogenization occurs in areas beyond those most frequently reported [10,21].…”
Section: Introductionmentioning
confidence: 99%
“…The richness and diversity in the 5H sampling line were observed to be the lowest. This was determined to be due to the fact that the lower effects of the sea resulted in the habitat of the 5H sampling line becoming more homogeneous (Zeng et al, 2017). Therefore, it was concluded that the homogeneity of the environmental conditions in the 5H sampling line had decreased the richness and diversity of the soil macro-faunal communities to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Estes resultados são semelhantes com os obtidos por Santos et al [17], que encontraram a diminuição de duração de vazões baixas e da frequência das vazões altas nos trechos de baixo São Francisco depois a construção dos principais reservatórios. Essa diminuição dos pulsos de baixa e alta leva a uma menor densidade das espécies de peixe, criando uma maior predação de outras espécies e atividade extrativista humana de pesca o que ocasiona escassez do recurso [38,39] e a introdução antrópica de espécies exóticas [36,[40][41][42]. O Grupo 5 dos indicadores avaliam a frequência de mudança das condições da água.…”
Section: Tabela 1 Dia Da Vazão Máxima E Mínima Segundo O Calendário unclassified